2017
DOI: 10.1039/c7ra08715b
|View full text |Cite
|
Sign up to set email alerts
|

Superior photocatalytic performance of LaFeO3/g-C3N4 heterojunction nanocomposites under visible light irradiation

Abstract: New types of LaFeO 3 /g-C 3 N 4 heterostructures were successfully prepared and the enhanced photocatalytic hydrogen evolution and degradation activities under visible light irradiation were determined. They possessed the features of a Z-scheme photocatalysis system. The photoexcited electrons on the conduction band of LaFeO 3 were transferred to the valence band of g-C 3 N 4 by the solid-solid intimately contacted interfaces, where the electrons and holes were recombined, and thus improved the separation of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(34 citation statements)
references
References 37 publications
1
33
0
Order By: Relevance
“…Thus, some doubts regarding the H2 production reported in their papers exist. Xu et al [39] reported hydrogen production activity over a LaFeO3/g-C3N4 composite in the presence of TEOA as a sacrificial reagent and Pt as a co-catalyst. Their results show that LaFeO3 alone had no activity due to the positive conduction band edge (0.11 V); hydrogen was only found if g-C3N4 (conduction band potential at -0.85 V vs. NHE) was added, which is in agreement of our results.…”
Section: Structural and Optical Characterization Of Lafeomentioning
confidence: 99%
“…Thus, some doubts regarding the H2 production reported in their papers exist. Xu et al [39] reported hydrogen production activity over a LaFeO3/g-C3N4 composite in the presence of TEOA as a sacrificial reagent and Pt as a co-catalyst. Their results show that LaFeO3 alone had no activity due to the positive conduction band edge (0.11 V); hydrogen was only found if g-C3N4 (conduction band potential at -0.85 V vs. NHE) was added, which is in agreement of our results.…”
Section: Structural and Optical Characterization Of Lafeomentioning
confidence: 99%
“…It was a promising photocatalysts with visible light response. Nowadays, LaFeO 3 /g-C 3 N 4 Z-scheme heterojunctions have been fabricated to promote the separation efficiency of photoinduced carriers and to enhance the photocatalytic activities [38]. The photocatalytic activities, including degradation performance and hydrogen evolution rate, of LaFeO 3 /g-C 3 N 4 heterojunctions were much higher than that of pure LaFeO 3 and g-C 3 N 4 under visible light irradiation [39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…For the success of such articial photosynthesis systems, however, the major challenge is the development of efficient visible-light active photocatalysts. [10][11][12] Graphitic carbon nitride (g-C 3 N 4 ), a polymeric semiconductor with a band gap of about 2.7 eV, has attracted signicant attention in recent years because of its excellent visible light response, 1,13,14 non-toxicity, low cost, and abundant raw materials. As a visible-light active photocatalyst, g-C 3 N 4 has been widely applied for photocatalytic degradation of pollutants, water splitting, and regeneration of NADH since 2009.…”
Section: Introductionmentioning
confidence: 99%